El teletrabajo y el Desempeño Laboral de los docentes en la Unidad Educativa Rafael Vásconez Gómez, 2021. - Manotoa Puente, Jhelsson Omar (2022)
The research project developed in the Educational Unit Rafael Vásconez Gómez of La Maná canton had as its purpose the realization of a descriptive study between teleworking and the labor performance of the teachers of the institution. The methodological approach of the research was quantitative, being necessary also the application of the deductive method. For the collection of statistical information, it was necessary the application of surveys, achieving results of 82 teachers on aspects of teleworking performed in the institution under the pandemic that has affected the planet. In the same way, were surveyed 146 students who contributed with the information to identify the existing relationships between the variables teleworking and job performance. The results show that 74% of teachers expressed little agreement that they do not have all the technological resources to perform their academic work. In relation to the communication of information with students, parents, and teachers, 61% expressed little agreement with this criterion. In relation to the results on the part of the students, 71% of them consider that they do not have all the technological equipment to receive the virtual classes, 53% say they have little agreement that their teachers do not justify their non-attendance to classes due to connectivity problems, and that the curricular contents developed in classes do not generate motivation for learning, 64% of the cases consider that they have little agreement with this criterion.